Memorandum of understanding between Universiti Teknologi MARA and People Friendship University of Russia (RUDN University) / Fakulti Perubatan - Universiti Teknologi MARA, Fakulti Perubatan (Universiti Teknologi MARA (UiTM), 2020)
UiTM and RUDN University will endeavour to strengthen, promote and develop cooperation on the basis of equality and mutual benefit.